أساليب ترشيد استخدام المياه المنزلية وعلاقتها ببعض المتغيرات دراسة تحليلية ميدانية في المحافظات الجنوبية الغربية من سورية - المعلولي ريمون فضل الله (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
مع ازدياد حاجة الأسرة السورية للمياه المنزلية، تبرز الحاجة لتعرف أساليب المرأة في ترشيد استهلاك المياه. السؤال الرئيس للبحث: ما الأساليب التي تتبعها المرأة السورية لترشيد استخدام المياه المنزلية ؟ وتركزت أهداف البحث في: - تعرف الأساليب التي تتبعها المرأة السورية(العينة) في ترشيد استخدام المياه المنزلية. - تحليل التباين بين أساليب ترشيد المياه تبعاً لمكان إقامة المرأة ومستواها التعليمي، والعلاقة بين تلك الأساليب وعمر المرأة وعملها، ودخلها. اتبع الباحث منهج تحليل المضمون، واستخدم عدد من الأدوات: معيار الترشيد، استبانة مقابلة موجهة ومفتوحة، وبطاقة تحليل. وتم التحقق من صدق وثبات الأدوات. مجتمع الدراسة الأسر المقيمة في المحافظات الجنوبية الغربية من سورية وعينة التحليل (778 بطاقة مقابلة). أفادت النتائج : بأن المرأة السورية (العينة) تمارس أساليب متنوعة لترشيد المياه المنزلية، توزعت على ستة أساليب مرتبة تنازلياً: البدائل(27.6%). التنظيم(23.6%). التدوير(23.3%). الضبط(18.3%). تقنية(6.0%). التوعية(1.2%). أشار تحليل التباين إلى وجود فروق جوهرية في أساليب الترشيد تبعاً لمتغير المحافظة، وكذلك تبعاً للمستوى التعليمي للمرأة. وأشار التحليل كذلك إلى وجود علاقة بين بعض أساليب الترشيد وعدد من خصائص المرأة.(العمر، العمل، الدخل المادي). وانتهى البحث بجملة مقترحات تدور بصورة أساسية حول: ضرورة تمكين المرأة من خلال اعتماد "التربية المائية" وبمشاركة من خلال مختلف أشكال التربية (النظامية، وغير النظامية، واللانظامية). With the increasing need of the Syrian family for domestic water, there is a need to improve the techniques of rationalization of water consumption methods followed by the women . The main question of research was: What are the techniques used by Syrian women to rationalize the consumption of household water? The objectives of the research focused on: 1. Identifying the techniques used by Syrian women in the rational consumption of domestic water. 2. Analyzing the difference between the techniques of rationalization of water depending on the place of residence and the level of education of women, and the relationship between those techniques and women’s age, job and income. The researcher followed content analysis method, and used a number of tools: - the rationalization standard, a direct and open interview questionnaire, and analysis card. The validity and reliability of tools were verified. The study population was the families living in the south-western provinces of Syria and the analysis sample was (778 interview card). the results showed that the Syrian women used a variety of techniques to rationalize the consumption of domestic water. They include six techniques, which are in descending order: alternatives (27.6%), organization (23.6%), recycling (23.3%), restriction (18.3%), technology (6.0%), and awareness (1.2%). Analysis of differences indicated that there were significant differences in the techniques of rationalization variables depending on the province, as well as depending on the level of education of women. The analysis showed as well the existence of a relationship between some of the techniques of rationalization and a number of other variables related to women; namely: age, job, and income. Research Recommendations: Qualifying women through the adoption of "water education" with the participation of various forms of education (formal education, non-formal education, and informal education).